2021
DOI: 10.3390/foods10051135
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Home Meal Replacement Product Containing Braised Mackerel (Scomber japonicus) with Radish (Raphanus sativus)

Abstract: The coronavirus disease pandemic has contributed to increasing convenience in food preferences. Home meal replacement (HMR) products are ready-to-eat, -cook, or -heat foods, providing convenience for consumers. We developed a HMR product containing mackerel as a protein- and lipid-rich source using various food-processing technologies to maintain its nutritional content and prolong shelf life. The HMR product contained mackerel, radish, and sauce in a ratio of 5:1:4. Raw frozen mackerels were thawed by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
4
10
0
Order By: Relevance
“…HFD was significantly different from the other thawing methods (p < 0.05). Similar results were reported by Negara et al [18] and Tirtawijaya et al [19]. The use of HFD successfully decreased the number of drip losses compared to conventional thawing methods.…”
Section: Drip Losssupporting
confidence: 87%
“…HFD was significantly different from the other thawing methods (p < 0.05). Similar results were reported by Negara et al [18] and Tirtawijaya et al [19]. The use of HFD successfully decreased the number of drip losses compared to conventional thawing methods.…”
Section: Drip Losssupporting
confidence: 87%
“…The drip loss after HFD was significantly lower (p < 0.05) than that of the other methods. This result is consistent with the results reported by Tirtawijaya et al [2], Negara et al [4], and Negara et al [5], who found that thawing via HFD resulted in a lower drip loss, as compared with conventional thawing methods.…”
Section: Drip Losssupporting
confidence: 92%
“…Seafood HMRs are one of the most popular products and have high demand because of their nutritional value, ease of preparation, and long shelf-life. Several studies have been conducted to develop seafood-based HMRs, including mackerel [2][3][4], a mixture of pen shell adductor muscles and common squid meat [5], and yellowfin sole (Pleuronectes aspera) [6]. While several types of seafood, such as the web-foot octopus, have the potential to become successful HMRs, seafood-based HMR products are still under development and have not yet been introduced to the market.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional composition of the processed mackerel was analyzed following the method of the Association of Official Analytical Chemists [21]. The fatty acid and amino acid profiles were obtained from standard chemicals based on the method described in a previous study [5]. The fatty acid contents of raw and processed CM were calculated to obtain the lipid quality indices, including hypocholesterolemic/hypercholesterolemic (h/H), atherogenic (AI), and thrombogenic (TI) indices, which were in turn calculated as described by Czech et al [22].…”
Section: Analysis Of Nutritional Compositionmentioning
confidence: 99%
“…CM is a source of valuable nutrition, such as proteins, lipids, and minerals, to humans [2,3]. It can be processed by various methods, including smoking, grilling, braising, canning, and frying [4][5][6][7]. Fried CM is a popular dish; in Korea, batter-fried CM is mixed with a special sauce to prepare Godeungo gangjeong.…”
Section: Introductionmentioning
confidence: 99%